2012
DOI: 10.1007/978-3-642-28148-8_5
|View full text |Cite
|
Sign up to set email alerts
|

The H $\imath$ L ε X System for Semantic Information Extraction

Abstract: In this paper, a new technique for the optimization of (partially) bound queries over disjunctive Datalog programs with stratified negation is presented. The technique exploits the propagation of query bindings and extends the Magic Set optimization technique (originally defined for non-disjunctive programs).An important feature of disjunctive Datalog programs is nonmonotonicity, which calls for nondeterministic implementations, such as backtracking search. A distinguishing characteristic of the new method is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…To better recognize named entities, we have utilized StanfordNER (http:// nlp.stanford.edu/software/CRF-NER.shtml), although during the tests, we also evaluated Alchemy (http://www.alchemyapi.com), DBpedia Spotlight (http:// dbpedia.org/spotlight), Extractiv (http://extractiv.com), OpenCalais (http: //www.opencalais.com), and Lupedia (http://www.old.ontotext.com/lupedia). The notion of semantic descriptors introduced in Section 4 has been inherited from HiLeX [10]. However, we have refined and extended their shape.…”
Section: Introductionmentioning
confidence: 99%
“…To better recognize named entities, we have utilized StanfordNER (http:// nlp.stanford.edu/software/CRF-NER.shtml), although during the tests, we also evaluated Alchemy (http://www.alchemyapi.com), DBpedia Spotlight (http:// dbpedia.org/spotlight), Extractiv (http://extractiv.com), OpenCalais (http: //www.opencalais.com), and Lupedia (http://www.old.ontotext.com/lupedia). The notion of semantic descriptors introduced in Section 4 has been inherited from HiLeX [10]. However, we have refined and extended their shape.…”
Section: Introductionmentioning
confidence: 99%
“…and nonmonotonic negation in bodies, ASP can express every query belonging to the complexity class Σ P 2 (NP NP ). Encouraged by the availability of efficient inference engines, such as DLV (Leone et al 2006), GnT (Janhunen et al 2006), Cmodels (Lierler 2005), or ClaspD (Drescher et al 2008), ASP has found several practical applications in various domains, including data integration (Leone et al 2005), semantic-based information extraction (Manna et al 2011;Manna et al 2012), e-tourism (Ricca et al 2010), workforce management (Ricca et al 2012), and many more. As a matter of fact, these ASP systems are continuously enhanced to support novel optimization strategies, enabling them to be effective over increasingly larger application domains.…”
Section: Introductionmentioning
confidence: 99%